Brachial Neuritis After Botulinum Toxin Injections for Cervical Dystonia: A Need for a Reappraisal?. Issue 2 (13th December 2018) - Cani, Ilaria; Latorre, Anna; Cordivari, Carla; Balint, Bettina; Bhatia, Kailash P.
Abstract: Background: Brachial neuritis has previously been described as a rare occurrence in patients receiving botulinum toxin for cervical or writing/focal arm dystonia. Methods: We report four cases of patients with a long history of cervical dystonia treated with botulinum toxin injections. Results: All patients developed pain and muscular weakness around the shoulder, with EMG studies suggesting brachial neuritis. Conclusions: In the context of these observations, we discuss the question of an association between brachial neuritis and botulinum toxin treatment.